Refill Drinking Water Depot Risk Assessment for Chemical Hazard Contaminant in 25 Cities of East Java Province, Indonesia - Yudied Agung Mirasa; Siti Nurhidayati; Wicaksono, Rania; Winarko, Winarko; Kholifah Firsayanti Juwono; Zainul Amiruddin Zakaria; Khuliyah Candraning Diyanah; Aditya Sukma Pawitra; Moch. Sahri (Universitas Airlangga, 2024)
Introduction: Water was a part of the environment that was very susceptible to contamination by various hazardous substances, both physical, chemical, and microbiological. Serious health problems might occur when humans consume contaminated drinking water and can cause infectious and non-infectious diseases. This study aimed to analyze the risk quotient of chemical hazard exposure in drinking water by depot refilling drinking water from 25 cities and regencies in East Java Province. Methods: This study was analytically observational with a cross-sectional research design. The sampling method used was porposive sampling, which took 25 from 38 cities and regencies in East Java province. There were three steps to analyze drinking water health risks: dose-response analysis, exposure path, and risk characteristics analyzed. Results and Discussion: The highest concentrations of each parameter parameter F (1.4132 mg/L), NO_3 (56.2780 mg/L), NO_2 (22,225 mg/L), Fe (0.3845 mg/L), Mg (4.54 mg/L), and Zn (0.4272 mg/L). Analysis of risk quotient > 1 for parameters NO_3 (1.2265), NO_2 (7,748), and Mg (1.1308) Indicates that drinking water in the area is not safe for consumption by people weighing 55kg as much as 2L/day for 350 days. Conclusion: Based on the results of studies conducted on those substances (F, NO_3, NO_2, Fe, Mg, and Zn) there are three substances in the water that have RQ value > 1, NO_3 (1.2265), NO_2 (7,748), and Mg (1.1308) this means that those substances are risking human health and needed to be addressed controlled.